Cell‐Based Therapy: Partial Coated Stem Cells with Bioinspired Silica as New Generation of Cellular Hybrid Materials (Adv. Funct. Mater. 29/2021). (16th July 2021) - Maciel, Marta M.; Correia, Tiago R.; Gaspar, Vítor M.; Rodrigues, João M. M.; Choi, Insung S.; Mano, João F.
Abstract : In article number 2009619, Tiago R. Correia, João F. Mano, and co‐workers develop a new type of hybrid cells. Individual human adipose‐derived mesenchymal stem cells are partially coated with a hard silica layer and display enhanced single‐cell survival and functionality in suspension conditions. Moreover, the ability of functionalizing silica backpacks unlocks the potential application of this novel system in a wide range of applications from biosensing to drug delivery and microtissue formation.